2006
DOI: 10.1007/s00268-005-0543-6
|View full text |Cite
|
Sign up to set email alerts
|

Islet Hyperplasia in Adults: Challenge to Preoperatively Diagnose Non‐Insulinoma Pancreatogenic Hypoglycemia Syndrome

Abstract: In patients with postprandial and/or fasting neuroglycopenia NIPHS may be suspected when insulin levels are low but inadequately suppressed and localization studies failed to show a distinct pancreatic tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 58 publications
(171 reference statements)
1
35
0
5
Order By: Relevance
“…In addition, it has already been observed that patients with nesidioblastosis can present a lower secretion of C-peptide and insulin than insulinoma patients (14,15), so that the diagnosis of nesidioblastosis is often more difficult than that of insulinomas. Moreover, it has been shown that patients with nesidioblastosis and even some rare glucose-sensitive insulinoma patients can undergo a 72-h fast test without hypoglycaemia (15), such patients being detected only with an oral glucose tolerance test (OGTT) or a meal test. In our study, proinsulin levels above 5 pmol/l during the fast test at the time of hypoglycaemia below 2.5 mmol/l appears to be the best criterion to make the diagnosis of endogenous hyperinsulinism with both 100% sensitivity and specificity.…”
Section: C-peptide Levels (Nmol/l)mentioning
confidence: 99%
“…In addition, it has already been observed that patients with nesidioblastosis can present a lower secretion of C-peptide and insulin than insulinoma patients (14,15), so that the diagnosis of nesidioblastosis is often more difficult than that of insulinomas. Moreover, it has been shown that patients with nesidioblastosis and even some rare glucose-sensitive insulinoma patients can undergo a 72-h fast test without hypoglycaemia (15), such patients being detected only with an oral glucose tolerance test (OGTT) or a meal test. In our study, proinsulin levels above 5 pmol/l during the fast test at the time of hypoglycaemia below 2.5 mmol/l appears to be the best criterion to make the diagnosis of endogenous hyperinsulinism with both 100% sensitivity and specificity.…”
Section: C-peptide Levels (Nmol/l)mentioning
confidence: 99%
“…Reluctance to routinely combine a glucose load or a test meal with the fasting test may be due to the notion that postprandial hypoglycemia may not be a real disease per se except for reactive adaptations as found in insulin-resistant obesity, early type-2 diabetes, or after gastric surgery [24]. Since description of the first patients with NIPHS [6][7][8] and the characteristic postprandial neuroglycopenia, the diagnostic workup of patients with a suspected hypoglycemic disorder has changed. We recently reported [8] that these patients also may demonstrate late fasting hypoglycemia, typically associated with detectable insulin levels that are inappropriately elevated in the presence of true biochemical hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Only a subgroup of patients with insulinoma demonstrates grossly elevated insulin levels as well as insulin secretion totally uncoupled to the ambient blood glucose concentration [4,5]. Furthermore, patients with non-insulinoma pancreatogenic hypoglycemia syndrome (NIPHS) present predominantly postprandial neuroglycopenia rather than fasting hypoglycemia associated with low insulin levels [6][7][8]. Diagnostic limits for insulin, C-peptide, proinsulin, and insulin surrogate parameters [9] according to the plasma glucose concentration have been thoroughly defined for the standard 72-h supervised fasting test.…”
Section: Introductionmentioning
confidence: 99%
“…Já foi demonstrado que pacientes com nesidioblastose podem apresentar teste de jejum prolongado de 72h negativo e que o diagnóstico dessa desordem é mais difícil em relação ao insulinoma, sendo necessá-ria, muitas vezes, a realização do TOTG de 5h (27). Raros são os casos de falso-negativo em pacientes com insulinoma relatados na literatura e cuja demonstração do estado hiperinsulinêmico e da hipoglicemia foi realizada mediante o TOTG de 5h (28,29) ou do teste pós-refeição mista (3).…”
Section: Em Nosso Estudo Foram Avaliados Os Aspectos Diagnós-ticos (Cunclassified